ANALISIS BEBAN PENYUSUTAN ASET TETAP DALAM UNDANG UNDANG PERPAJAKAN ATAS PPh BADAN - Sunyatama, Yohana Dini; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is a qualitative research in the form of analysis of financial statements and the lists of fixedassets. The sample is the lists of all fixed assets which are owned by the company and the financial statements ofPT. Bagoes Tjipta Karya. The result of the research shows that the company has applied straight-line depreciationmethod for all fixed assets with 8 years useful life. The researcher analyzes the calculation of depreciation expenseby comparing the calculation of depreciation expense of fixed assets which is based on Financial AccountingStandards and tax law at PT Karya Bagoes Tjipta The amount of income tax in accordance with FinancialAccounting Standards in 2013-2015 periods is amounted to Rp. 154,146,781 whereas according to the provisionsof the tax law is amounted to Rp. 148,927,007 so there is a difference about Rp. 5,219,774.It can be concluded thatthe company has already applied the depreciation method in accordance with Financial Accounting Standards andtax law i.e. the straight line method, but there is an error to the depreciation tariff of each rate of fixed assets, inwhich it leads to the changes in the company profits which give an impact on the amount of Corporate Income Taxwhich has to be paid by PT Karya Bagoes Tjipta.Keywords: income taxes, depreciation, corporate income tax